The role of glutamate dehydrogenase in the ageing brain - Zhou, Tao; Wang, Haichuan (Frontiers in Pharmacology, 2025)
The homeostasis of glutamate, the primary excitatory neurotransmitter in the brain and is crucial for normal brain function. The mitochondrial enzyme glutamate dehydrogenase (GDH) connects the multifunctional amino acid glutamate, which is intimately related to glutamate metabolism, to the Krebs cycle. As a result, GDH reglutes the synthesis and uptake of the chemical messenger glutamate in neuroendocrine cells, playing a crucial role in the metabolism of proteins and carbohydrates. Nonetheless, brain ageing and numerous neurodegenerative diseases, including Parkinson’s disease and Alzheimer’s disease, have been linked to GDH malfunction or dysregulation. In this review, we summarize the dynamics of GDH levels in the ageing brain and provide additional details about the role of GDH in the ageing brain. Understanding the metabolic mechanisms underlying glutamate homeostasis in the aging brain and how GDH regulates glutamate-dependent metabolic processes at synapses may lead to novel therapeutic approaches for neurodegenerative and psychiatric disorders, potentially slowing the aging process and promoting brain regeneration.